Assessment of Sealing Ability and Degradation Resistance of a Hydrogel‐Based Root Canal Filling Material Using a Bacterial Leakage Model and SEM Analysis. - Ellermann, Else; Richter, Daniel; Punzano, Ignasi Belda; Schmocker, Andreas; Bispinghoff, Mark; Eyüboğlu, Tan Fırat; Özcan, Mutlu; Klug, Yoel A. (BioMed Research International, 2026)
Background: This study evaluated the sealing ability and degradation resistance of a novel hydrogel‐based, low‐viscosity, light‐curable obturation material compared with gutta‐percha combined with an epoxy resin–based sealer using a bacterial leakage model and scanning electron microscopy (SEM) analysis. Methods: Thirty‐seven extracted single‐rooted bovine incisors were allocated into four groups: gutta‐percha + epoxy resin sealer (n = 12), hydrogel‐based material (n = 10), positive control with empty canals (n = 11), and negative control (n = 4). Bacterial leakage was assessed using a two‐chamber model inoculated with Enterococcus faecalis. Survival times were analyzed using nonparametric tests. For degradation analysis, 30 hydrogel specimens (n = 6 per medium) were incubated in phosphate‐buffered saline (PBS), brain heart infusion (BHI) broth, E. faecalis suspension, sterile‐filtered saliva, or pH 10 carbonate buffer. SEM‐based Feret diameter measurements were obtained after 1, 8, and 30 days and analyzed using Kruskal–Wallis and Holm‐adjusted Mann–Whitney U tests. Results: The first leakage occurred after 11 days in the gutta‐percha group and after 58 days in the hydrogel group. Forty percent failure was observed after 22 days for gutta‐percha and after 121 days for the hydrogel material (p < 0.001). Mean Feret diameter increased most markedly under alkaline conditions (Δ = +0.100 μm from Day 1 to Day 30; p < 0.001), whereas changes in PBS, BHI, E. faecalis, and saliva remained below 0.05 μm over 30 days. Conclusions: The hydrogel‐based obturation material demonstrated significantly prolonged resistance to bacterial penetration and maintained structural stability under biologically relevant incubation conditions. Further long‐term and in vivo studies are required to confirm clinical performance.